The Impact of Exchange Rate and Exchange Rate Volatility on Foreign Direct Investment: An Econometric Investigation in Sri Lanka - Thujiyanthan, Priyatharsiny (Asian Journal of Managerial Science, 2021)
This paper aims to explore the impact of exchange rate volatility on the ability to attract foreign direct investment (FDI) in the emerging economy of Sri Lanka. This investigation covers the period between 1978 and 2018. Exchange rate volatility is captured from the variance of the residuals by employing the testing procedure of ARCH (Engle, 1982) and GARCH (Bollerslev, 1986) models and its impact upon FDI is estimated by an Autoregressive Distributed Lag (ARDL) approach which is developed by Pesaren et al. (2001). The estimated results indicated that exchange rate volatility exerted significant positive impact on FDI during the period between 1978 and 2018 and the results show that exchange rate, exchange rate volatility, inflation, infrastructure, local and foreign interest rate, real GDP, political stability, and trade openness are the crucial determinants of FDI inflow in Sri Lanka. These findings are supported with Goldberg and Kolstad (1994) and it helps to the policy makers to concentrate exchange rate volatility, other macro-economic stability and political stability are key to boom FDI inflow in Sri Lanka.